Gut Microbiome and its Role in the Development of Neurological Disorder (Schizophrenia) - Ayesha Ameen, Muhammad Nadeem Akram, Sana Farooq, Mehreen Fatima, Hassan Raza, Rabia Naz, Umer Aziz, Mariyam Aziz, Syed Tahir, Athar Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The gut microbiome, defined as the community of microorganisms residing in the digestive tract, is believed to play a crucial role in the development of neurological disorders, including schizophrenia. Design: Recent research indicates that individuals with schizophrenia have altered gut microbiomes, characterized by reduced levels of beneficial bacteria such as Bifidobacterium and Lactobacillus, and increased levels of potentially harmful bacteria, such as Proteobacteria. Findings: Furthermore, studies show that the communication between the gut and the brain, known as the gut-brain axis, is disrupted in individuals with schizophrenia. While the exact mechanisms underlying the association between the gut microbiome and schizophrenia are not yet fully understood, researchers suggest that changes in the gut microbiome may affect the immune system and neurotransmitters, which in turn contribute to the development of the disorder Practical Implication: Targeting the gut microbiome through interventions like probiotics and the Mediterranean diet may offer a promising therapeutic approach for individuals with schizophrenia. Keywords: Gut Microbiome. Microbiota, Immune cells, Schizophrenia